Pelatihan Siswa Menengah Kejuruan (SMK) Kesehatan Menggunakan Aplikasi Kalkulator Pacu Tumbuh Balita: Pengabdian - Haripin Togap Sinaga; Mincu Manalu; Effendi Nainggolan; Berlin Sitanggang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Determining the nutritional status of toddlers is an important activity in posyandu. However, the skills of Posyandu cadres are still low, especially in using nutritional application. The existence of vocational students can be empowered to assist cadres at Posyandu.This community service activity involved 20 vocational students. They were trained on how to measure height, mid upper arm circumference and head circumference and use the Pacu Tumbuh Calculator application. Each student took anthropometric measurements at the Posyandu and assessed the nutritional status of children based on height for age, MUAC for age and height for age indices. The total number of children measured was 80 children. Before the training, almost all students did not have skill in doing anthropometric measurements and using the nutritional calculator application. After the training, all (100%) students were skilled in using calculator application, 90% were skilled in assessing nutritional status and 80% were skilled in determining the form of children's food. Around 25% of children under five were stunting. A total 25,0% children stunted and 16.3% were categorized middle MUAC. Vocational students can be used to caders in posyandu to carry out anthropometric measurements and nutritional status assessments.